Preparation and characterization of vemurafenib microemulsion based hydrogel using surface active ionic liquid - Mohammed Jasim Neamah; Entidhar Jasim Muhammed Al-Akkam (Pensoft Publishers, 2024)
Cancer is considered the second leading cause of death worldwide. Skin melanomas account for the highest mortality rate amongst all types of skin cancer. Systemic treatment with vemurafenib has a high rate of adverse effects, so attempts have been made to prepare a topical form of this drug. Microemulsions have been used to improve drug delivery to the skin. The microemulsions were prepared by dissolving vemurafenib in a mixture of peppermint oil and Smix, followed by the addition of water. The characteristics and effectiveness of surface-active ionic liquid-based vemurafenib microemulsions were characterised and evaluated in vitro. The vemurafenib microemulsions (CP5, CP7 and CP8) had droplet sizes in the microemulsion range (less than 200 nm), and they were used to prepare microemulsion-based hydrogels using HPMC K15M via the hot and cold method. The prepared microemulsion-based hydrogels were then evaluated. The microemulsion-based hydrogel GP5 exhibited higher skin deposition (45.4%) than the other hydrogels; thus, GP5 is a promising candidate for the topical treatment of melanoma by vemurafenib.